2006
DOI: 10.1080/08957950601104955
|View full text |Cite
|
Sign up to set email alerts
|

No evidence of metallic methane at high pressure

Abstract: Recently reported superconductivity in lithium under pressure has renewed the interest in hydrogen and hydrogen-rich systems in the long standing quest for room temperature superconductivity. As the required metallization of pure hydrogen cannot be achieved within current experimental capabilities, it has been suggested that the chemical precompression exerted by heavier atoms in compounds with a large hydrogen content should lower the required pressures to attain the metallic transition in these alloys. Follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 27 publications
0
10
1
Order By: Relevance
“…All of them show up interesting new structures and novel properties under pressure. CH 4 is still an insulator up to the pressure of 520 GPa4. Although Eremets et al experimentally reported the metallization and superconductivity of SiH 4 above 60 GPa5, for the controversial result it might be understood as superconductivity of amorphous silicon, silicon hydrides, or platinum hydrides67.…”
mentioning
confidence: 99%
“…All of them show up interesting new structures and novel properties under pressure. CH 4 is still an insulator up to the pressure of 520 GPa4. Although Eremets et al experimentally reported the metallization and superconductivity of SiH 4 above 60 GPa5, for the controversial result it might be understood as superconductivity of amorphous silicon, silicon hydrides, or platinum hydrides67.…”
mentioning
confidence: 99%
“…4,5 Hydrogen can be viewed in these systems as being "chemically precompressed," which lowers the metallization pressure. While the conditions for forming metallic methane have not been reached experimentally, 6 recent theoretical studies predict that both SiH 4 ͑Refs. 5 and 7͒ and GeH 4 ͑Ref.…”
Section: Introductionmentioning
confidence: 99%
“…By way of example we present in Figure 4 the electronic density of states (DOS) calculated for Phases VII and VIII at 300 GPa (the corresponding band structures are in the SM). We emphasize that the overall DOS is very much free-electron like in a three dimensional context; in the DOS there is no sign of the gap (as in the case of CH 4 ) or pseudo-gap found in calculations on other EH 4 systems (E = Si, Ge, Sn) [14,21,22,23,24,25,26].…”
mentioning
confidence: 99%